Efficacy of Unani Therapeutic Interventions in Pediatric Nocturnal Enuresis (Bawl fi’l Farāsh): A Case Series - Bano, Uzma (Journal of Neonatal Surgery, 2024)
Background: Bawl fi’l Farāsh (nocturnal enuresis) is a common pediatric disorder associated with significant clinical and psychosocial consequences. Longitudinal studies indicate that nearly 20% of children in early school years’ experience occasional nocturnal enuresis, while approximately 4% have bed-wetting episodes two or more times per week. The condition is more prevalent in boys than in girls; population-based studies from the United States report prevalence rates of 9% and 7% among boys aged 7 and 10 years, respectively, compared with 6% and 3% among girls of the same age groups. In India, the prevalence of nocturnal enuresis ranges between 7% and 12.6%. According to Unani medical principles, the condition arises from the predominance of Ruṭūbat (excessive moist temperament), leading to Istirkhā’-e-A‘ḍā’ of Mathana (laxity of urinary bladder musculature). Methods: A prospective case series was conducted on five pediatric patients diagnosed with primary nocturnal enuresis at the Pediatrics (Unani) OPD of Majeedia Unani Hospital, New Delhi. Comprehensive clinical evaluation ruled out congenital anomalies and organic pathology. Patients were treated with Unani pharmacotherapy along with structured behavioral counseling for a duration of eight weeks. Psychosocial and family histories were also assessed. Results: All patients demonstrated significant clinical improvement during the treatment period. Complete remission of bed-wetting episodes was observed in all cases by the end of eight weeks. No adverse effects related to the therapy were reported. A family history of psychological stress was noted in several patients. Conclusion: This case series suggests that Unani therapeutic interventions, combined with behavioral counseling, are safe and effective in managing primary nocturnal enuresis and may substantially improve the quality of life in affected children